Determinación de parásitos en dos diferentes densidades de siembra de tilapia roja Oreochromis spp) en un sistema “RAS” en el municipio del Tambo (Cauca) (2021)
The present study aimed to determinate the frequency of ectoparasites that affect the production of red tilapia (Oreochromis spp) in a recirculating aquaculture system (RAS), in the town of Tambo (Cauca); at fish farm "Lago Manizales", using two stocking rate (15kg / m3 and10kg / m3 ). Red tilapia (Oreochromis spp) fingerlings were used for this work. This species being of great economic importance at national and international level. Therefore, it is necessary to have studies that show us what stocking rate should be used so that the product is safe and guarantees the health of the consumer. In this case, microorganisms of the genus Oodinium were observed in the two stocking rates with the highest prevalence in the dorsal and caudal fin. In addition, in the stocking rate of (15kg / m3 ) in the last shipment that was carried out, 4 parasites of Icht multifillis were observed in the water. Through descriptive statistics analysis in the first sampling was observed that in the stocking rate of 15kg / m3 ), there was an incidence of Oodinium in 83.33% in the caudal fin, and in the stocking rate of 10kg / m3 , in the dorsal fin was 53.85%. In the second sampling in the density of 15kg / m3 , there was an incidence of 76.47% in the caudal fin, and in the density of 10kg / m3 , it was presented in 100% in the caudal. Through an analysis of variance (ANOVA) it was determined that there were no significant differences between the treatments, according to the densities studied, with T1 corresponding to 600 fish density and T2 density 400 fish